Do neighbourhoods influence how parents and children interact? Direct observations of parent–child interactions within a large Australian study. (March 2023) - Bennetts, Shannon K; Love, Jasmine; Bennett, Clair; Burgemeister, Fiona; Westrupp, Elizabeth M; Hackworth, Naomi J; Mensah, Fiona K; Levickis, Penny; Nicholson, Jan M
Highlights: 594 parents and children completed a play-based observation at home. Families resided in 148 different postcodes, of varying socioeconomic status. Observations were rated on parent sensitive responding and parent–child mutuality. Greater neighbourhood disadvantage was associated with less sensitive responding. Parenting supports tailored to local community are required. Abstract: Neighbourhood-level factors can exert unique influence on children's development, independent of individual parent, child, and family factors. We investigated the contribution of neighbourhood socioeconomic status (using government-generated definitions) to directly-observed parent–child interactions among 596 Australian parents and their 7–8-year-old children. Parents' sensitive responding and parent–child positive mutuality were rated according to the SCARP:7 – 8 Years (Short Coding of Attachment-Related Parenting). Adjusting for individual family characteristics, multilevel modelling revealed evidence of an association between neighbourhood socioeconomic status and sensitive responding ( β =.10, p= .004 ) but not for parent–child positive mutuality ( β =−.01, p =.90). Tailored, evidence-based parenting supports according to local community need are warranted.